2022
DOI: 10.1002/er.8519
|View full text |Cite
|
Sign up to set email alerts
|

Amino‐functionalized SiO 2 modified porous polyetherimide separator for high performance Li‐S batteries

Abstract: As one of the most promising energy storage systems, the application of lithium sulfur battery is hindered by low ionic conductivity, poor thermal stability, and a serious shuttle effect of polysulfide species of commercial polyolefin separators. Herein, a kind of novel porous polyetherimide (PEI) based separator (IAPEI-4) with excellent heat resistance and electrochemical properties was prepared. Briefly, by grafting amino group (-NH 2 ) onto the surface of SiO 2 , highly dispersed amino-functionalized SiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…The calculations showed that the binding energy of -NH2 and PF 6 .was 4.27 eV, which was stronger than that of other natural materials, such as cellulose and chitin [30,36]. This indicates that -NH2 limits the migration of anions in liquid electrolyte, thereby allowing relatively easier Li + transport [33]. Separators as inactive components in LIBs should have good electrochemical stability within a wide voltage range.…”
Section: Electrochemical Performancesmentioning
confidence: 96%
See 1 more Smart Citation
“…The calculations showed that the binding energy of -NH2 and PF 6 .was 4.27 eV, which was stronger than that of other natural materials, such as cellulose and chitin [30,36]. This indicates that -NH2 limits the migration of anions in liquid electrolyte, thereby allowing relatively easier Li + transport [33]. Separators as inactive components in LIBs should have good electrochemical stability within a wide voltage range.…”
Section: Electrochemical Performancesmentioning
confidence: 96%
“…To improve Li + transport in natural biomass nanofiber-based separators, the porosity and pore structure can be adjusted by using a pore former during the formation. However, the reported pore formers such as nano-silica particles may result in an increase in the weight of the separator [33]. To address this issue, researchers tend to change the diameters of the fibers to adjust the porosity and pore size of the separators.…”
Section: Introductionmentioning
confidence: 99%